Effect of buffer in prestarter on calf performance - K.J. Jordan; J.L. Morrill; P.G. Reddy; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1985)
Previous work at the Kansas Agricultural Experiment Station contributed to the development of an early weaning program (see 1984 Dairy Day, Report of Progress 460). This program involves the use of a prestarter, which is a specially prepared feed intended to encourage early dry feed consumption and rumen development. Because all of the carbohydrate in the prestarter is lactose and because the rumen of the very young calf is not adapted to utilization of starch, rapid fermentation might cause excessive acidity in the developing rumen, a condition that might be avoided by adding a buffer to the prestarter. This experiment was conducted to test that hypothesis.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Buffer; Calf performance; Feed consumption; Prestarter; Weight gain